The Merchant's Philosophy as the Foundation for Effective and Efficient Islamic Education - Edi Sugianto; Abdul Hamid Arribathi; Suryan widati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Effective and efficient Islamic education is evidenced by the success of Islamic da'wah in the 18th century, namely with the establishment of the Islamic kingdom in Indonesia. For that, it needs to be excavated. The purpose of this research is to prove by obtaining an overview and explanation that the merchant philosophy is able to color and make a blueprint for Islamic education in Indonesia, where the era began, merchants succeeded in carrying out Islamic da'wah which was the initial form of Islamic education based on determination, imitating the Prophet as a da'wah command from Allah, and competing in goodness (fastabikul khairat). This research is a qualitative-discipitive type. The methods used are literature review and historical-philosophical analysis. Literature review is carried out by collecting and analyzing concepts about educational goals (general and Islamic), effective and efficient meanings, and merchant philosophy. Historical Analysis is used to review the history of the spread of Islam in the archipelago by merchants as an early form of successful Islamic education, as well as the role of merchants in the establishment and development of Islamic organizations such as Muhammadiyah and NU. The findings in this study are that the philosophy of merchants of that era is the forerunner and foundation of effective and efficient Islamic education. The impact of this research is that the study of history needs to be echoed so that the optimism of building Islamic education continues to burn so that it is felt by the present and future generations.